Linking Entrepreneurial Competencies and Financial Risk: Pathways to Sustainable Business Growth - Miguel, Donald Cyndyl; Gemina, Rosalie (Journal of Interdisciplinary Perspectives, 2024)
This study explores the relationship between entrepreneurial skills and financial risk tolerance among ambulant vendors operating in informal economies. Focusing on key competencies such as self- competency, risk management, and control focus, the research aims to determine how these skills influence vendors’ willingness to engage in financial risks, a vital factor for business growth and sustainability. Data collected from 152 ambulant vendors in Agusan del Sur was analyzed using Pearson’s correlation and multiple regression. The results show a strong positive correlation between entrepreneurial skills and financial risk tolerance, with self-competency emerging as the most influential factor. With higher self- efficacy, entrepreneurs are more sure of handling financial uncertainty and grabbing chances. The study emphasizes acquiring entrepreneurial competencies to improve financial decision-making and corporate resilience. It also emphasizes the importance of focused training initiatives to improve these competencies, therefore providing information for stakeholders and legislators endorsing unofficial economies.